200m and 400m long sprints drills - Khmel, M. (The Best of British Track & Field Drills Series, 2009)
Beginning with basic running drills, Coach Michael Khmel begins with back kick drills to focus on low leg recovery form. Along with the low leg focus, Khmel shares strategies for attaining and maintaining a tall posture for ideal running form. He adds high heels followed by high knees to complete drilling the components of the running stride. Khmel moves to the mechanics of proper arm movement with stationary arm motion that focuses on keeping the shoulders stable while maintaining proper motion. He also details the ideal arm angles during the running motion. Adding arm motion to the running stride completes the proper running form. In the next segment, Running the Bend, Khmel presents a long sprint drill sequence that teaches techniques and strategies for the proper form in the bend in order to allow maximizing speed out of the curve. Khmel's coaching of the demonstrators throughout the presentation offers invaluable information on how to see and correct errors that long sprinters commonly make in the 200M and 400M long sprints.